EKSPLORASI KEBUDAYAAN TAHLIL DALAM PERSPEKTIF AGAMA ISLAM DAN MASYARAKAT DI INDONESIA - Fenita Oktaviani Rachmat; Hisny Fajrussalam; Adelina Rizkyta Nuramalia; Elmalia Futri; Rifa Sani Alfazriani (Institut Dirosat Islamiyah Al-Amien Prenduan Sumenep, 2022)
The article entitled Tahlil Culture in the Perspective of Islam and Society, Perspective is the process of organizing various sensations into a meaningful pattern in responding to a problem. There are various kinds of culture in Indonesia related to the teachings of Islam. Before the spread of Islamic teachings in Indonesia, people were very bound by traditions that had been passed down from generation to generation. Many Hindu-Buddhist teachings were still attached at that time. Until Islam spread widely which was brought by Wali Songo. They spread Islam in various ways. They use customs that have been embedded in society by inserting Islamic teachings in their spread. Tahlilan is a culture that has existed for a long time, carried out by Muslims, especially in Indonesia, which has become a part of the life of the community, but the problem lies in the perspective of different people about whether or not it is permissible to carry out the tahlilan tradition. The law of tahlilan is permissible (permissible), as long as what is done does not include things that deviate from Islamic law, because the content of the tahlilan activity itself is reading the holy verses of the Qur'an, reading Thayyibah sentences, dhikr, Tasbik, Tahmid, Tahlil, Read Shalawat to the Prophet Muhammad SAW and end by reading the Du'a. The method used in this study is qualitative, namely the data used in the form of words and survey results to find out how the community's perspective on the tahlilan tradition is. Then the data collected is in the form of a survey from the community via a google form link. The results of this study draw a conclusion that shows that people carry out the tahlilan tradition to pray for someone who has died.